PENGARUH BIMBINGAN BELAJAR BAGI SISWA DALAM MENGHADAPI PENILAIAN AKHIR SEMESTER PADA MATA PELAJARAN BIOLOGI - Ade Suryanda; Eka Putri Azrai; Leni Melisa (Universitas Majalengka, 2020)
Readiness is an important factor that every person must have in order to be able to carry out activities thoroughly and optimally. Students must have readiness in facing the final exam. This study aims to determine the effect of student participation in tutoring on student readiness in facing the final exam. The research was conducted at Public High School Cibinong. The research method used was ex post facto. The population of this study was all students of class XI in Public High School Cibinong. The sample used in this study was 70 XI students majoring in Natural Sciences who were taken by proportional random sampling. After testing the prerequisites, the research data is normally distributed and homogeneous. The results of the hypothesis test conducted using the Smith-Satterthwaite formula in the data two weeks before the test obtained the Smith-Satterthwaite t value of 0.47. This means that there is an effect of student participation in tutoring on readiness to face biology final exam test. In the data taken one day before the assessment the Smith-Satterthwaite t value was obtained 0.85 which means that there was no influence of student participation in tutoring on the readiness to face the final examination of the biology.